Decision-Making and Multisensory Combination Under Time Stress. (July 2021) - Sun, Yile; Sekuler, Robert
Using a video game platform, we examined how vision-based decision making was affected by a concurrent, potentially conflicting auditory stimulus. Electroencephalographic responses showed that by 150 milliseconds of stimulus onset, the brain had detected the conflict between visual and auditory stimuli. Systematically reducing the intertrial interval (ITI), which subjects described as stressful, undermined decision making. Subjects' arterial pulse variance decreased along with ITI, signaling increased parasympathetic influence on the heart. When successive trials required a shift in processing mode, short ITIs significantly boosted one trial's influence on the next, suggesting that stress reduces cognitive flexibility. Finally, our study demonstrates the heart's and the brain's important influence on decision making.